A Guide for Understanding Health Education and Promotion Programs. Issue 2 (March 2018) - Kim, Richard W.; Nahar, Vinayak K.
Planning, Implementing & Evaluating Health Promotion Programs: A Primer is a versatile and comprehensive resource on the theoretical and practical underpinnings of successful health promotion programs. The requirements for effective health promotion program development are presented with frequent use of practical planning examples, pedagogical devices, and expert rationale. Ideal for undergraduate and graduate students in health education, promotion, and planning courses, this 15-chapter textbook is organized in a manner that specifically addresses the responsibilities and competencies required of health education specialists as published in the Health Education Specialist Practice Analysis of 2015. The authors of this textbook are leaders in the field and provide readers with the skills necessary to carry out the full process of health promotion program execution, while also offering direct preparation for CHES and MCHES licensing exams.